War and Peace in the Worlds of Rudolf H. Sauter A Cultural History of a Creative Life. - Reznick, Jeffrey S. (Anthem Press, 2022)
War and Peace in the Worlds of Rudolf H. Sauter is the first book to examine the creative life and worlds of Rudolf H. Sauter (1895-1977), the German-born artist, poet, cultural observer and nephew of the famed novelist John Galsworthy. It reveals him as a creative figure in his own right who produced an intriguing body of artistic and literary work.